2023
DOI: 10.3389/fimmu.2023.1082050
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training-attenuated insulin resistance and liver injury in elderly pre-diabetic patients correlates with NLRP3 inflammasome

Abstract: BackgroundDiabetes is one of the most common metabolic diseases and continues to be a leading cause of death worldwide. The NLRP3 inflammasome has been shown to exert detrimental effects on diabetic models. However, evidence linking NLRP3 inflammasome and pre-diabetes has been scarcely explored. Herein, we aimed to determine whether the NLRP3 inflammasome correlates with insulin resistance and liver pathology in a cohort of pre-diabetic subjects.Methods50 pre-diabetic subjects were randomly assigned to a Pre-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The study found that high sensitivity CRP and IL-18 decreased and IL-10 increased in DM patients in the exercise group compared with the control group. 263 12 weeks of Tai chi training 264 or 6 months of exercise 265 could decrease the activity of NLRP3 inflammasome and related inflammatory cytokines like IL-1β and IL-18 in prediabetic patients to alleviate systemic inflammation, reduce blood glucose, and improve IR. A single dose of high-intensity interval training (HIIT) had obvious anti-inflammatory effects on patients with T2DM, which was characterized by the decrease of TNF-α and TLR2 surface protein.…”
Section: Healthy Diet and Exercisementioning
confidence: 99%
“…The study found that high sensitivity CRP and IL-18 decreased and IL-10 increased in DM patients in the exercise group compared with the control group. 263 12 weeks of Tai chi training 264 or 6 months of exercise 265 could decrease the activity of NLRP3 inflammasome and related inflammatory cytokines like IL-1β and IL-18 in prediabetic patients to alleviate systemic inflammation, reduce blood glucose, and improve IR. A single dose of high-intensity interval training (HIIT) had obvious anti-inflammatory effects on patients with T2DM, which was characterized by the decrease of TNF-α and TLR2 surface protein.…”
Section: Healthy Diet and Exercisementioning
confidence: 99%
“…Although the role of NLRP3 in the exercise regulation of diabetic skeletal muscle is still unclear, recent studies have confirmed that the NLRP3 inflammasome is related to the pathogenesis of T2DM, and that by inhibiting inflammasome activation in adipose tissue and the liver, it can enhance insulin signaling [45]. Exercise training may reduce insulin resistance and liver injury in elderly prediabetic subjects by inhibiting the activity of the NLRP3 inflammasome [46].…”
Section: Mcc950 Treatment and Aerobic Exercise Moderates The Levels O...mentioning
confidence: 99%
“…Evidence shows that 12 weeks of Tai Chi intervention effectively alleviated glucose homeostasis and inhibited the expression of the NLRP3 inflammatory signal pathway in middle-aged and elderly pre-diabetic patients ( 107 ). Moreover, the combined of Yijinjing and resistance training has proven effective in inhibiting the robust NLRP3 inflammasome activation, thereby alleviating insulin resistance and liver injury in elderly pre-diabetes ( 108 ). Research has also shown that exercise can exert an anti-inflammatory effect by reducing circulating levels of inflammasome activation-related inflammatory cytokines IL-1β and IL-18 in overweight/obese populations ( 109 ).…”
Section: Exercise On Improving Diabetic Complications By Targeting Py...mentioning
confidence: 99%